Molecular etiology of atherogenesis--in vitro induction of lipidosis in macrophages with a new LDL model - Estronca, Luís (2012)
Background: Atherosclerosis starts by lipid accumulation in the arterial intima and progresses into a chronic vascular inflammatory disease. A major atherogenic process is the formation of lipid-loaded macrophages in which a breakdown of the endolysomal pathway results in irreversible accumulation of cargo in the late endocytic compartments with a phenotype similar to several forms of lipidosis. Macrophages exposed to oxidized LDL exihibit this phenomenon in vitro and manifest an impaired degradation of internalized lipids and enhanced inflammatory stimulation. Identification of the specific chemical component(s) causing this phenotype has been elusive because of the chemical complexity of oxidized LDL. Methodology/Principal Findings: Lipid ‘‘core aldehydes’’ are formed in oxidized LDL and exist in atherosclerotic plaques. These aldehydes are slowly oxidized in situ and (much faster) by intracellular aldehyde oxidizing systems to cholesteryl hemiesters. We show that a single cholesteryl hemiester incorporated into native, non-oxidized LDL induces a lipidosis phenotype with subsequent cell death in macrophages. Internalization of the cholesteryl hemiester via the native LDL vehicle induced lipid accumulation in a time- and concentration-dependent manner in ‘‘frozen’’ endolysosomes. Quantitative shotgun lipidomics analysis showed that internalized lipid in cholesteryl hemiester-intoxicated cells remained largely unprocessed in those lipid-rich organelles. Conclusions/Significance: The principle elucidated with the present cholesteryl hemiester-containing native-LDL model, extended to other molecular components of oxidized LDL, will help in defining the molecular etiology and etiological hierarchy of atherogenic agents.